Сryosurgery and autoplasty of a segmental defect of the 1st metatarsal bone for a giant-cell carcinoma - Demichev, Nikolay; Sitkalieva, Fatima; Khalagummaev, Kadi (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
The article describes a clinical case of damaging the 1st metatarsal bone on the left foot with a giant-cell carcinoma in a female patient at the age of 48. The authors showed efficacy of cryosurgery and osteoplasty for treatment of this pathology.